A scoping review of rehabilitation interventions for survivors of head and neck cancer. Issue 17 (14th August 2019) - Rodriguez, Ana Maria; Komar, Alyssa; Ringash, Jolie; Chan, Catherine; Davis, Aileen M.; Jones, Jennifer; Martino, Rosemary; McEwen, Sara
Abstract: Purpose : The objectives of this scoping review were to summarize, understand, and disseminate findings from a broad body of literature on rehabilitation interventions used with survivors of head and neck cancer. Method : Searches were conducted in six databases. Inclusion criteria were studies of adult head and neck cancer survivors with a predefined primary rehabilitation outcome as a result of an intervention. Excluded were studies not written in English, opinion papers, or studies where the intervention was not carried out by a rehabilitation healthcare service. A second level, full-text review of the studies was conducted. A thematic analysis was used to examine and combine study findings. Results : A total of 3804 results were retrieved from all sources resulting in 39 papers that were analyzed. The thematic analysis of the included papers represented interventions focusing on swallowing and nutrition, speech, physical therapy, assistive devices, complementary and alternative modalities, comprehensive interdisciplinary programs, and preventive rehabilitation programs. Conclusion : This review has provided an overview of the scope of rehabilitation interventions available for survivors of head and neck cancer and preliminary information about their efficacy. This is foundational information for the development and refinement of rehabilitation interventions and programs for head and neck cancer survivors. Implications for Rehabilitation: The existing evidence suggests that survivors of head and neck cancer can benefit from early screening of potential rehabilitation needs and being involved in preventive rehabilitation programs pre-surgery when possible. Rehabilitation programs should consider swallowing interventions for patients as evidence reports improved swallowing function, decreased pain and discomfort, and reduced duration of feeding tube use. Rehabilitation programs should consider nutritional interventions after radiotherapy: Patients benefited from stabilized weights, improved nutritional status, and an improved quality of life. Physical exercise interventions demonstrated improvements in physical function, muscular endurance, range of motion, overall quality of life, and showed reductions in pain, and fatigue.